The Effect of Return on Asset (ROA), Current Ratio (CR) and Debt to Equity Ratio (DER) on Stock Prices With Dividend Policy as an Intervening Variable - Diki Prianda; Eka Nurmala Sari; Muis Fauzi Rambe (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2022)
This study aims to determine, test and analyze the effect of ROA, CR, DER on stock prices with dividend policy as an intervening variable in basic and chemical industrial manufacturing companies for the period 20152019. This research is an associative quantitative research using documentation techniques. The population of this study amounted to 75 company. Research sample of 11 companies by using purposive sampling techniques and using SmartPLS as methode data analysis. The results showed that ROA, DER had a negative and insignificant relationship to stock prices. CR has a negative and significant relationship to stock prices. ROA, CR have a positive and insignificant relationship with dividend policy. DER has a positive and significant relationship to dividend policy. Dividend policy has a negative and significant relationship to stock prices. Dividend policy is not able to mediate the effect of ROA, CR, DER on stock prices.